Alterations in Excitatory and Inhibitory Synaptic Development Within the Mesolimbic Dopamine Pathway in a Mouse Model of Prenatal Drug Exposure - Taylor Boggess; James C. Williamson; Ethan B. Niebergall; Hannah Sexton; Anna Mazur; Richard D. Egleton; Lawrence M. Grover; W. Christopher Risher (Frontiers Media S.A., 2021)
The rise in rates of opioid abuse in recent years in the United States has led to a dramatic increase in the incidence of neonatal abstinence syndrome (NAS). Despite improved understanding of NAS and its acute symptoms, there remains a paucity of information regarding the long-term effects of prenatal exposure to drugs of abuse on neurological development. The primary goal of this study was to investigate the effects of prenatal drug exposure on synaptic connectivity within brain regions associated with the mesolimbic dopamine pathway, the primary reward pathway associated with drug abuse and addiction, in a mouse model. Our secondary goal was to examine the role of the Ca+2 channel subunit α2δ-1, known to be involved in key developmental synaptogenic pathways, in mediating these effects. Pregnant mouse dams were treated orally with either the opioid drug buprenorphine (commonly used in medication-assisted treatment for substance use patients), gabapentin (neuropathic pain drug that binds to α2δ-1 and has been increasingly co-abused with opioids), a combination of both drugs, or vehicle daily from gestational day 6 until postnatal day 11. Confocal fluorescence immunohistochemistry (IHC) imaging of the brains of the resulting wild-type (WT) pups at postnatal day 21 revealed a number of significant alterations in excitatory and inhibitory synaptic populations within the anterior cingulate cortex (ACC), nucleus accumbens (NAC), and medial prefrontal cortex (PFC), particularly in the buprenorphine or combinatorial buprenorphine/gabapentin groups. Furthermore, we observed several drug- and region-specific differences in synaptic connectivity between WT and α2δ-1 haploinsufficient mice, indicating that critical α2δ-1-associated synaptogenic pathways are disrupted with early life drug exposure.